MEDIA PEMBELAJARAN ADMINISTRASI PAJAK BERBASIS VIDEO ANIMASI 2 DIMENSI DI SMK NEGERI 1 BANGLI - I Made Cristian Arta Kusuma; Christina Purnama Yanti; Ketut Laksmi Maswari (Jurnal Teknologi Informasi dan Komputer, 2022)
ABSTRACTDuring the Covid-19 pandemic, teaching and learning activities at SMK Negeri 1 Bangli implemented Hybrid teaching and learning activities. This learning activity makes the subject of Tax Administration less attractive to students of Accounting study program. Because when learning is online, the delivery of material is felt to be less accurate. So we need teaching media that helps explain material related to Tax Administration to students. The media is a 2-dimensional animated video-based learning media. This research uses primary and secondary data collection methods. Primary data collection used the interview method with one of the teachers of the Accounting study program at SMK Negeri 1 Bangli and the questionnaire method by giving statements to students of class XI Accounting study program at SMK Negeri 1 Bangli as many as 80 people and the statements given to material experts and media experts. Secondary data collection using the library method. Based on the results of data processing, it was found that 90% or around 72 students stated that they could receive the related material well. Then the voice of the narrator in this 2-dimensional animated video-based learning media can be heard clearly. The conclusions obtained after this Learning Media were tested, the results obtained were in accordance with the author's expectations. This learning media has succeeded in helping teachers deliver the material and can be well received by students.Keywords: pandemic, hybrid, media, animation, 2dABSTRAKSelama pandemi Covid-19 berlangsung, kegiatan belajar mengajar di SMK Negeri 1 Bangli memberlakukan kegiatan belajar mengajar Hybrid. Kegiatan belajar ini menjadikan mata pelajaran Administrasi Pajak kurang menarik minat siswa prrodi Akuntansi. Hal itu dikarenakan saat pembelajaran daring, penyampaian materi dirasa kurang akurat. Sehingga diperlukan media ajar yang membantu menjelaskan materi terkait Administrasi Pajak kepada siswa. Media tersebut adalah media pembelajaran berbasis video animasi 2 dimensi. Peneitian ini menggunakan metode pengumpulan data primer dan data sekunder. Pengumpulan data primer menggunakan metode Wawancara dengan salah satu guru prodi Akuntansi di SMK Negeri 1 Bangli dan metode Kuesioner dengan memberikan penyataan kepada siswa kelas XI prodi Akuntansi di SMK Negeri 1 Bangli sebanyak 80 orang dan adanya pernyataan yang diberikan kepada ahli materi dan ahli media. Pengumpulan data sekunder menggunakan metode kepustakaan. Berdasarkan hasil pengolahan data, didapatkan sebanyak 90% atau sekitar 72 siswa menyatakan dapat menerima materi terkait dengan baik. Kemudian suara narator yang ada pada media pembelajaran berbasis video animasi 2 dimensi ini dapat didengar dengan jelas. Kesimpulan yang didapatkan setelah Media Pembelajaran ini diujikan, hasil yang diperoleh sesuai dengan harapan penulis. Media pembelajaran ini berhasil membantu guru menyampaikan materi dan dapat diterima oleh siswa dengan baik.Kata Kunci: pandemi, hybrid, media, animasi, 2d